2022
DOI: 10.1097/ta.0000000000003593
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl malonate slows succinate accumulation and preserves cardiac function in a swine model of hemorrhagic shock

Abstract: BACKGROUND: Succinate (SI) is a citric acid cycle metabolite that accumulates in tissues during hemorrhagic shock (HS) due to electron transport chain uncoupling. Dimethyl malonate (DMM) is a competitive inhibitor of SI dehydrogenase, which has been shown to reduce SI accumulation and protect against reperfusion injury. Whether DMM can be therapeutic after severe HS is unknown. We hypothesized that DMM would prevent SI buildup during resuscitation (RES) in a swine model of HS, leading to better physiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…[8][9][10][11][12] In both small and large animal models of hemorrhagic shock and resuscitation, our group showed that DMM can protect against damage to the pulmonary endothelial glycocalyx. 2,5 This study is the first to examine the therapeutic use of a malonate ester in an acute lung injury model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[8][9][10][11][12] In both small and large animal models of hemorrhagic shock and resuscitation, our group showed that DMM can protect against damage to the pulmonary endothelial glycocalyx. 2,5 This study is the first to examine the therapeutic use of a malonate ester in an acute lung injury model.…”
Section: Discussionmentioning
confidence: 99%
“…2 This may be related to using a direct lung injury model, rather than an ischemia-reperfusion model, as seen with myocardial infarction or hemorrhagic shock injury models. 2,8 However, the present study is the first to show that succinate is produced in the pulmonary vasculature endothelium in a model of acute lung injury and that DMM reduces succinate accumulation in this model (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations